Breaking the shell : voyaging from nuclear refugees to people of the sea in the Marshall Islands - Genz, Joseph H. (University of Hawaiʻi Press, 2018)
On the atoll of Rongelap in the northern seas of the Marshall Islands, apprentice navigators once learned to find their way across the ocean by remotely sensing how islands transform the patterning of swell and currents. Renowned for their instructional stick charts that model and map the interplay of islands and waves, these students of wave piloting techniques embarked on trial voyages to ruprup jo̧kur, a Marshallese expression roughly translated as "breaking the shell" of the turtle, which would confer their status as navigators. These traditional practices, already in decline with imposing colonial occupations, came to an abrupt halt with the Cold War-era nuclear weapons testing program conducted by the United States. The residents and their descendants are still trying to recover from the myriad environmental, biological, social, and psychological impacts of the nuclear tests. Breaking the Shell presents the journey of Captain Korent Joel, who, having been forced into exile from the near-apocalyptic thermonuclear Bravo test of 1954, has reconnected to his ancestral maritime heritage and forged an unprecedented path toward becoming a navigator. Paralleling the Hawaiian renaissance that centered on Nainoa Thompson learning from Satawalese navigator Mau Piailug, the beginnings of the Marshallese voyaging revitalization--a collaborative, community-based project spanning the fields of anthropology, history, and oceanography--involved blending scientific knowledge systems, resolving ambivalence in nearly forgotten navigational techniques, and deftly negotiating cultural protocols of knowledge use and transmission. Through Captain Korent's own voyaging trial, he and a group of surviving mariners from Rongelap are, against one of the darkest hours in human history, "breaking the shell" of their prime identity as nuclear refugees to begin recovering their most intimate of connections to the sea. Ultimately these efforts would inaugurate the return of the traditional outrigger voyaging canoe for the greater Marshallese nation, an achievement that may work toward easing ethnic tensions abroad and ensure cultural survival in their battle against the looming climate change-induced rising ocean. Drawing attention to cultural rediscovery, revitalization, and resilience in Oceania, the Marshallese are once again celebrating their existence as a people born to the rhythms of the sea.